Analysis Of The Influence Of Digital Marketing Strategy Through Search Engine Optimization (SEO) In Increasing Sales Of Msme Products In Indonesia - Owen De Pinto Simanjutak; Roberto Roy Purba (UNIVED Press, 2024)
This research aims to analyze digital marketing strategies through Search Engine Optimization (SEO) in increasing product sales. The object of this research is MSME actors in Indonesia. The inscriptors used in digital marketing are Accessibility, Interactivity, Entertainment, Credibility, Irritation, Informativeness. This type of research is a descriptive research with a quantitative approach and the analysis used is a partial Least Square (PLS) model analysis carried out by evaluating the outer model and evaluating the inner model. The number of respondents representing MSME actors was 150 respondents. The results of the study show that Accessibility has a significant positive effect on Product Sales. Accessibility has no positive and insignificant effect on SEO (Search Engine Optimization). Credibility has a positive but not significant effect on Product Sales. Credibility has a significant positive effect on SEO (Search Engine Optimization). Entertainment has a significant positive effect on Product Sales. Entertainment has a positive but not significant effect on SEO (Search Engine Optimization). Informativeness has a significant positive effect on Product Sales. Informativeness has a significant positive effect on SEO (Search Engine Optimization). Interactivity has a positive but not significant effect on Product Sales. Interactivity has a positive but not significant effect on SEO (Search Engine Optimization). Irritation had a positive but not significant effect on Product Sales. Irritation has a significant positive effect on SEO (Search Engine Optimization).